MANAGEMENT OF A PATIENT WITH ANKYLOSING SPONDYLITIS TYPE SPONDYLOARTHRITIS AND LATENT TUBERCULOSIS INFECTION - Nadhya Allia; Lita Diah Rahmawati (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Ankylosing spondylitis (AS) is one of the most common types of spondylarthritis (SpA) and Disease-Modifying Antirheumatic Drug (DMARD) is one of the modalities for treating the disease. An increased risk of latent tuberculosis infection (LTBI) reactivation in rheumatic patients receiving DMARD has been reported. Management of patients with rheumatic diseases who are also infected with LTBI needs to be understood in order not tobecome active TB. We reported a case of a 57-year-old man with AS. Patient was planned to be treated with DMARD so that hepatitis and TB screening performed. It was discovered that this patient had LTBI. The prophylactic therapy for TB was given. DMARD therapy started 1 month after TB prophylactic therapy was given. For monitoring the disease progression,anamnesis, physical, laboratory, and radiology examination performed regularly.